HUBUNGAN PENGETAHUAN DENGAN PEMERIKSAAN INSPEKSI VISUAL ASETAT PADA WANITA USIA SUBUR - Mega Rahmawati, Ria Muji Rahayu (Akbid Wirabuana, 2023)
IVA is one of the early detection of cervical cancer by using acetate acid 3-5% by inspect and seen with direct eye observation. This examination is painless, easy, cheap and the results are immediate. The purpose of this study is to determine the education related to the behavior of women of childbearing on IVA examination in the Sukaraja Nuban Public Health Center working area in 2023. The research will be conducted based on quantitative research. The population are all women of childbearing age in working area Sukaaraja Nuban Public Heath Center East Lampung withpopulation are 4950 women. The sample of the research is 370 people or respondent. Statistical test in this study using Chi Square test with 95% CI and P value less than 0,05 were considered statistically significant. The result of this research are 96,2% responden that did not check and 48,4% respondents have lower level of knowledge. Based on the result of chi square statistic test known that P value is 0,020, less than 0,05 (P value <0,05), there is correlation of knowledge level with behavior of IVA examination on women of childbearing age in Sukaraja Nuban Public Health Center working areaEast Lampung in 2023 with OR = 5,933 (1,309-26,892). So, It is suggested to health workers at the Sukaraja Nuban Heath Center to continuously increase outreach to the community to increase public knowledge about IVA examination to encourage people’s behavior to want to carry out IVA examination.Keywords : Knowledge, Visual Acetate Inspection